Method for preparing carbon nano tube by adopting catalytic pyrolysis asphalt

The preparation of carbon nanotubes by catalytic pyrolysis asphalt method solves the problems of high production costs and poor product performance in the prior art, and realizes the preparation of high-quality carbon nanotubes, and is safe in the process and low in cost.

CN119797338APending Publication Date: 2025-04-11XIAN THERMAL POWER RES INST CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510022760.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The methods for preparing carbon nanotubes in the prior art have problems such as high cost, complex process and poor product performance. In particular, chemical vapor deposition methods require dangerous gas sources and high temperatures, which increase the preparation cost.

Method used

Carbon nanotubes are prepared by catalytic pyrolysis of asphalt. By mixing the asphalt powder with the catalyst powder, dispersing it in a volatile solvent, pyrolyzing and cleaning in an acid solution, high-quality carbon nanotubes are finally obtained.

Benefits of technology

The carbon nanotubes prepared by this method have a large aspect ratio, smooth surface, few impurities, good conductivity, safe process, low cost and high yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797338A_ABST
    Figure CN119797338A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of carbon nanotubes, and discloses a method for preparing carbon nanotubes by catalytic pyrolysis of asphalt, which comprises the following steps: asphalt powder and catalyst powder are uniformly mixed to obtain a mixture A, and the mass ratio of the catalyst powder to the asphalt powder in the mixture A is (0.25-0.45): 3; uniformly dispersing the mixture A in a volatile solvent to obtain a mixed solution A; volatilizing the volatile solvent in the mixed solution A, and drying to obtain a mixture B; pyrolyzing the mixture B in a protective atmosphere to obtain a crude product carbon nanotube; and reacting the crude product carbon nanotube with an acid solution, and after the reaction is finished, cleaning and drying to obtain a final product carbon nanotube. The carbon nano tube prepared by the preparation process is relatively large in length-diameter ratio, relatively smooth in surface, relatively few in impurities and relatively good in conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon nanotube preparation, and in particular relates to a method for preparing carbon nanotubes by catalytic pyrolysis of asphalt. Background Art

[0002] Nanotubes are particularly ideal quasi-one-dimensional quantum materials with unique structures. Their unique structures and related mechanical, electronic and chemical properties have broad application prospects in the fields of lithium batteries, catalysis, medicine and many electronic devices. However, the current method for preparing carbon nanotubes mainly uses chemical vapor deposition, which uses dangerous gas sources and metal catalysts to react in a fluidized bed to obtain carbon nanotubes. The gas sources used are expensive in terms of transportation and storage, and the temperature required during the reaction is high, which undoubtedly increases the cost of preparing carbon nanotubes. Therefore, there is an urgent need for a simple, safe and low-cost strategy to prepare carbon nanotubes.

[0003] Chinese patent application CN113772659A discloses a method for preparing carbon nanotubes by in-situ pyrolysis of coal tar pitch, which involves reacting coal tar pitch with a catalyst (a catalyst containing transition metals such as Fe, Co, and Ni). However, the carbon nanotubes prepared by this method have a small aspect ratio, contain many impurities, and have a rough surface. Therefore, the performance of the carbon nanotubes prepared by this method (such as electrical conductivity) is not high enough. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing carbon nanotubes by catalytic pyrolysis of asphalt. The carbon nanotubes prepared by the preparation process of the present invention have a relatively large length-to-diameter ratio, a relatively smooth surface, fewer impurities, and better conductivity.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing carbon nanotubes by catalytic pyrolysis of asphalt, comprising the following steps: The asphalt powder and the catalyst powder are mixed to obtain a mixture A, wherein the mass ratio of the catalyst powder to the asphalt powder in the mixture A is (0.25-0.45):3; Dispersing the mixture A evenly in a volatile solvent to obtain a mixed solution A; volatilize the volatile solvent in the mixed solution A and dry it to obtain a mixture B; The mixture B is pyrolyzed under a protective atmosphere to obtain crude carbon nanotubes; The crude carbon nanotubes are reacted with an acid solution, and after the reaction is completed, they are washed and dried to obtain final carbon nanotubes.

[0006] Preferably, the catalyst powder is copper acetate powder.

[0007] Preferably, 0.34-0.36 g of copper acetate powder is added for every 3 g of asphalt powder.

[0008] Preferably, the mesh size of the asphalt powder is above 100 meshes, and the mesh size of the catalyst powder is between 40 and 50 meshes.

[0009] Preferably, when the mixture B is pyrolyzed under a protective atmosphere, the pyrolysis temperature is 950-1050° C. and the pyrolysis time is 2-3 h.

[0010] Preferably, when the crude carbon nanotubes are reacted with the acid solution, the crude carbon nanotubes are immersed in a hydrochloric acid solution for the reaction.

[0011] Preferably, the concentration of the hydrochloric acid solution is 0.9-1.1 mol / L, and the soaking time is 4-6 h.

[0012] Preferred: The volatile solvent is anhydrous ethanol. When the mixture A is evenly dispersed in the volatile solvent, every 3.75-3.45 g of the mixture A is mixed with 20-40 mL of anhydrous ethanol. Ultrasonic dispersion is used in the dispersion process, the ultrasonic power is 60-80 W, and the ultrasonic time is 10-30 min. When the mixture B is pyrolyzed under a protective atmosphere, the protective atmosphere is nitrogen, and the flow rate of the nitrogen is 200-230 mL·min -1 .

[0013] Preferred: When the volatile solvent in the mixed solution A is evaporated and dried, a constant temperature water bath is used for drying, the drying temperature is 74-76° C., and the drying time is 2-3 hours; The crude carbon nanotubes are reacted with an acid solution, and after the reaction is completed, they are washed and dried until neutral, and the drying temperature is 70-90° C. to remove moisture.

[0014] The present invention also provides a carbon nanotube, which is prepared by the method for preparing carbon nanotubes by catalytic pyrolysis of asphalt as described above.

[0015] The present invention has the following beneficial effects: The present invention controls the amount of catalyst powder and asphalt powder, and reacts the crude product carbon nanotubes with an acid solution. Experiments have shown that the final product carbon nanotubes obtained by the present invention are relatively regular in morphology and free of impurity residues, have a relatively large aspect ratio, high conductivity and high yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1This is a scanning electron microscope photograph of the carbon nanotubes prepared in Example 1 of the present invention.

[0017] Figure 2 This is a scanning electron microscope photograph of the carbon nanotubes prepared in Comparative Example 1 of the present invention.

[0018] Figure 3 This is a scanning electron microscope photograph of the carbon nanotubes prepared in Comparative Example 2 of the present invention.

[0019] Figure 4 This is a scanning electron microscope photograph of the carbon nanotubes prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0020] According to the technical solution of the present invention, without changing the essential spirit of the present invention, a person skilled in the art can propose a variety of interchangeable structures and implementations. Therefore, the following specific implementation methods and drawings are only examples of the technical solution of the present invention and should not be regarded as the entirety of the present invention or the limitation of its technical solution.

[0021] The method for preparing carbon nanotubes by catalytic pyrolysis of asphalt comprises the following steps: Step 1) First, weigh a certain amount of catalyst powder and add it to the ground asphalt powder according to the weight ratio. After mixing evenly, place it in a beaker, wherein the mesh size of the asphalt powder is not less than 100 meshes. In the following embodiments of the present invention, the asphalt powder used is asphalt powder after passing through a 100-mesh sieve.

[0022] Step 2) Add a certain amount of anhydrous ethanol to the beaker and stir until uniform, then place the beaker in an ultrasonic cleaner for a certain period of time to evenly disperse the catalyst powder and the asphalt powder to obtain a dispersion; Step 3) The beaker is placed in a constant temperature water bath to evaporate the anhydrous ethanol and dry it, and then the remaining sample in the beaker is placed in a corundum ark, and then the corundum ark is placed in a high-temperature tube furnace filled with nitrogen, and the high-temperature tube furnace is heated to a certain temperature for pyrolysis to obtain a crude product carbon nanotubes; Step 4) Soaking the obtained crude carbon nanotubes in an acid solution for a certain period of time, taking them out after soaking, washing them, and drying them to obtain the final carbon nanotubes.

[0023] In the above scheme of the present invention, in step 1), the mass ratio of the catalyst powder to the asphalt powder is (0.25~0.45):3; more preferably, the mass ratio of the catalyst powder to the asphalt powder is 0.35:3; in the embodiment of the present invention, the catalyst is copper acetate powder, which is weighed in grams during the experiment, and the error of the weighing equipment is ±0.01g, so the above optimal ratio is actually a small range, that is, (0.34-0.36):3. The mesh number of the catalyst copper acetate powder is 40~50 mesh. Wherein, the amount of anhydrous ethanol added is 20~40mL; more preferably, the amount of anhydrous ethanol added is 30mL. In step 2), the ultrasonic cleaning instrument is ultrasonicated for 10~30min, wherein the ultrasonic power is 60-80W; more preferably, the ultrasonic cleaning instrument is ultrasonicated for 20min. In step 3), the drying is carried out in a constant temperature water bath at 74-76°C for 2-3 hours. After the constant temperature water bath is set to a certain temperature, there will actually be a certain deviation. For example, if the set temperature is 75°C, the actual temperature will be 74-76°C. More preferably, the drying is carried out in a constant temperature water bath for 3 hours. In step 3), the flow rate of N2 is 200-230 mL•min -1 More preferably, the flow rate of N2 is 200 mL·min -1 . In step 3), the temperature of the pyrolysis reaction is 950~1050℃, and the pyrolysis time is 2-3h; more preferably, the temperature of the pyrolysis reaction is 1000℃. In step 4), the obtained crude carbon nanotubes are soaked in an acid solution; more preferably, the obtained crude carbon nanotubes are soaked in a 0.9-1.1mol / L hydrochloric acid solution for 4-6h; more preferably, the obtained carbon nanotubes are soaked in a 1mol / L hydrochloric acid solution for 5h. In step 4), the obtained soaked carbon nanotubes are washed to neutrality and dried at 70~90℃ to finally obtain carbon nanotubes; more preferably, the obtained soaked carbon nanotubes are washed to neutrality and dried at 80℃ to finally obtain carbon nanotubes.

[0024] Embodiment 1: The method for preparing carbon nanotubes by catalytic pyrolysis of asphalt in this embodiment includes the following steps: Weigh 0.35 of copper acetate powder and add 3 g of ground asphalt powder (the asphalt powder is the undersize after passing through a 100-mesh sieve). Mix the mixture of copper acetate powder and asphalt powder evenly with a ball mill and place it in a beaker. Add 40 mL of anhydrous ethanol to the beaker and stir until evenly mixed. Then place the beaker in an ultrasonic cleaner for 35 minutes at an ultrasonic power of 70 W. Then place the beaker in a constant temperature water bath at 75 °C and dry it for 5 hours. Then place the remaining sample in the beaker in a corundum ark and place the corundum ark in a nitrogen bath with a flow rate of 220 mL • min.-1 The crude carbon nanotubes were placed in a high-temperature tube furnace and heated to 1000°C at a heating rate of 5°C / min for pyrolysis at a constant temperature for 2.5 h. The crude carbon nanotubes were obtained after cooling to room temperature. The crude carbon nanotubes were soaked in a 1 mol / L hydrochloric acid solution for 5 h, washed to neutrality, and then dried at 80°C to obtain the final carbon nanotubes.

[0025] like Figure 1 As shown, the final product carbon nanotubes obtained in this embodiment are relatively regular in morphology, free of impurities, and relatively slender in overall shape, with a high aspect ratio, high electrical conductivity and a high yield.

[0026] Embodiment 2: The method for preparing carbon nanotubes by catalytic pyrolysis of asphalt in this embodiment includes the following steps: Weigh 0.25 of copper acetate powder and add 3 g of ground asphalt powder (the asphalt powder is the undersize after passing through a 100-mesh sieve). Mix the mixture of copper acetate powder and asphalt powder evenly with a ball mill and place it in a beaker. Add 40 mL of anhydrous ethanol to the beaker and stir until evenly mixed. Then place the beaker in an ultrasonic cleaner for 35 minutes at an ultrasonic power of 75 W. Place it in a constant temperature water bath at 75 °C and dry it for 5 hours. Then place the remaining sample in the beaker in a corundum ark and place the corundum ark in a nitrogen bath at a flow rate of 220 mL • min. -1 The crude carbon nanotubes were placed in a high-temperature tube furnace and heated to 1000°C at a heating rate of 5°C / min for constant temperature pyrolysis for 2.5 h. The crude carbon nanotubes were obtained after cooling to room temperature. The crude carbon nanotubes were soaked in a 0.9 mol / L hydrochloric acid solution for 5 h, washed to neutrality, and then dried at 90°C to obtain the final carbon nanotubes.

[0027] Embodiment 3: The method for preparing carbon nanotubes by catalytic pyrolysis of asphalt in this embodiment includes the following steps: Weigh 0.45 of copper acetate powder and add 3 g of ground asphalt powder (the asphalt powder is the undersize after passing through a 100-mesh sieve). Mix the mixture of copper acetate powder and asphalt powder evenly with a ball mill and place it in a beaker. Add 40 mL of anhydrous ethanol to the beaker and stir until evenly mixed. Then place the beaker in an ultrasonic cleaner for 35 minutes at an ultrasonic power of 75 W. Then place the beaker in a constant temperature water bath at 75 °C and dry it for 5 hours. Then place the remaining sample in the beaker in a corundum ark and place the corundum ark in a nitrogen bath with a flow rate of 220 mL • min. -1The crude carbon nanotubes were placed in a high-temperature tube furnace and heated to 1000°C at a heating rate of 5°C / min for constant temperature pyrolysis for 2.5 h. The crude carbon nanotubes were obtained after cooling to room temperature. The crude carbon nanotubes were soaked in a 1.1 mol / L hydrochloric acid solution for 5 h, washed to neutrality, and then dried at 70°C to obtain the final carbon nanotubes.

[0028] Embodiment 4: The method for preparing carbon nanotubes by catalytic pyrolysis of asphalt in this embodiment includes the following steps: Weigh 0.35 of copper acetate powder and add 3 g of ground asphalt powder (the asphalt powder is the undersize after passing through a 100-mesh sieve). Mix the mixture of copper acetate powder and asphalt powder evenly with a ball mill and place it in a beaker. Add 40 mL of anhydrous ethanol to the beaker and stir until evenly mixed. Then place the beaker in an ultrasonic cleaner for 35 min, where the ultrasonic power is 75W; then place the beaker in a constant temperature water bath at 75 ℃ and dry for 5 h. Then place the remaining sample in the beaker in a corundum ark, and then place the corundum ark in a nitrogen flow rate of 220 mL • min -1 The crude carbon nanotubes were placed in a high-temperature tube furnace and heated to 950°C at a heating rate of 5°C / min for 2.5 h. The crude carbon nanotubes were obtained after cooling to room temperature. The crude carbon nanotubes were soaked in a 1 mol / L hydrochloric acid solution for 5 h, washed to neutrality, and then dried at 80°C to obtain the final carbon nanotubes.

[0029] Embodiment 5: The method for preparing carbon nanotubes by catalytic pyrolysis of asphalt in this embodiment includes the following steps: Weigh 0.35 of copper acetate powder and add 3 g of ground asphalt powder (the asphalt powder is the undersize after passing through a 100-mesh sieve). Mix the mixture of copper acetate powder and asphalt powder evenly with a ball mill and place it in a beaker. Add 40 mL of anhydrous ethanol to the beaker and stir until evenly mixed. Then place the beaker in an ultrasonic cleaner for 35 minutes at an ultrasonic power of 80 W. Then place the beaker in a constant temperature water bath at 75 °C and dry it for 5 hours. Then place the remaining sample in the beaker in a corundum ark and place the corundum ark in a nitrogen bath with a flow rate of 220 mL • min. -1 The crude carbon nanotubes were placed in a high-temperature tube furnace and heated to 1050°C at a heating rate of 5°C / min for 2.5 h. The crude carbon nanotubes were obtained after cooling to room temperature. The crude carbon nanotubes were soaked in a 1 mol / L hydrochloric acid solution for 5 h, washed to neutrality, and then dried at 85°C to obtain the final carbon nanotubes.

[0030] Embodiment 6: The method for preparing carbon nanotubes by catalytic pyrolysis of asphalt in this embodiment includes the following steps: Weigh 0.35 of copper acetate powder and add 3 g of ground asphalt powder (the asphalt powder is the undersize after passing through a 100-mesh sieve). Mix the mixture of copper acetate powder and asphalt powder evenly with a ball mill and place it in a beaker. Add 40 mL of anhydrous ethanol to the beaker and stir until evenly mixed. Then place the beaker in an ultrasonic cleaner for 35 minutes at an ultrasonic power of 70 W. Then place the beaker in a constant temperature water bath at 75 °C and dry it for 5 hours. Then place the remaining sample in the beaker in a corundum ark and place the corundum ark in a nitrogen bath with a flow rate of 220 mL • min. -1 The crude carbon nanotubes were placed in a high-temperature tube furnace and heated to 1000°C at a heating rate of 5°C / min for 2 hours. The crude carbon nanotubes were obtained after cooling to room temperature. The crude carbon nanotubes were soaked in a 1.1 mol / L hydrochloric acid solution for 5 hours, washed to neutrality, and then dried at 80°C to obtain the final carbon nanotubes.

[0031] Embodiment 7: The method for preparing carbon nanotubes by catalytic pyrolysis of asphalt in this embodiment includes the following steps: Weigh 0.35 of copper acetate powder and add 3 g of ground asphalt powder (the asphalt powder is the undersize after passing through a 100-mesh sieve). Use a ball mill to mix the mixture of copper acetate powder and asphalt powder evenly, and then place it in a beaker. Add 40 mL of anhydrous ethanol to the beaker, and then stir until evenly mixed. Then place the beaker in an ultrasonic cleaner for 35 minutes, where the ultrasonic power is 65W; then place the beaker in a constant temperature water bath at 75 °C and dry for 5 hours. Then place the remaining sample in the beaker in a corundum ark, and then place the corundum ark in a nitrogen flow rate of 220 mL • min -1 The crude carbon nanotubes were placed in a high-temperature tube furnace and heated to 1000°C at a heating rate of 5°C / min for 3 hours. The crude carbon nanotubes were obtained after cooling to room temperature. The crude carbon nanotubes were soaked in a 0.9 mol / L hydrochloric acid solution for 5 hours, washed to neutrality, and then dried at 85°C to obtain the final carbon nanotubes.

[0032] The conductivity data of the final product carbon nanotubes prepared in the above embodiment was tested, and the specific data is shown in Table 1.

[0033] Table 1

[0034] As can be seen from Table 1, the above scheme of the present invention can obtain carbon nanotubes with high conductivity and high yield by controlling the amount of appropriate catalyst and the carbonization temperature.

[0035] Comparative Example 1: The method for preparing carbon nanotubes in this comparative example comprises the following steps: Weigh 0.35 of cobalt chloride powder and add 3 g of ground asphalt powder (the asphalt powder is the undersize after passing through a 100-mesh sieve). Mix the mixture of cobalt chloride powder and asphalt powder evenly with a ball mill and place it in a beaker. Add 40 mL of anhydrous ethanol to the beaker and stir until evenly mixed. Then place the beaker in an ultrasonic cleaner for 35 minutes at an ultrasonic power of 60 W. Then place the beaker in a constant temperature water bath at 75 °C and dry it for 5 hours. Then place the remaining sample in the beaker in a corundum ark and place the corundum ark in a nitrogen bath with a flow rate of 220 mL • min -1 The crude carbon nanotubes were placed in a high-temperature tube furnace and heated to 1000°C at a heating rate of 5°C / min for 3 hours. The crude carbon nanotubes were obtained after cooling to room temperature. The crude carbon nanotubes were soaked in a 1 mol / L hydrochloric acid solution for 5 hours, washed to neutrality, and dried to obtain the final carbon nanotubes.

[0036] like Figure 2 As shown, the final product carbon nanotubes obtained in this comparative example are relatively messy in morphology, with a large number of particles existing, which are presumed to be catalyst particles, and the aspect ratios are not uniform and vary greatly. It can be seen that different catalyst types have a great influence on the morphology of carbon nanotubes.

[0037] Comparative Example 2: The method for preparing carbon nanotubes in this comparative example comprises the following steps: Weigh 0.35 of nickel acetate powder and add 3 g of ground asphalt powder (the asphalt powder is the undersize after passing through a 100-mesh sieve). Mix the mixture of copper acetate powder and asphalt powder evenly with a ball mill and place it in a beaker. Add 40 mL of anhydrous ethanol to the beaker and stir until it is evenly mixed. Then put the beaker in an ultrasonic cleaner for 35 minutes, where the ultrasonic power is 75W; then put the beaker in a constant temperature water bath at 75 ℃ and dry it for 5 hours. Then put the remaining sample in the beaker into a corundum ark, and then put the corundum ark in a nitrogen flow rate of 220mL •min -1 The crude carbon nanotubes were placed in a high-temperature tube furnace and heated to 1000°C at a heating rate of 5°C / min for 3 hours. The crude carbon nanotubes were obtained after cooling to room temperature. The crude carbon nanotubes were soaked in a 1 mol / L hydrochloric acid solution for 5 hours, washed to neutrality, and dried to obtain the final carbon nanotubes.

[0038] like Figure 3As shown, the carbon nanotubes obtained in the comparative example have a relatively curly morphology, are not uniform in shape, and have a relatively serious agglomeration phenomenon. It can be seen that different ultrasonic powers have a great influence on the morphology of carbon nanotubes.

[0039] Comparative Example 3: The method for preparing carbon nanotubes in this comparative example comprises the following steps: Weigh 0.35 of nickel acetate powder and add 3 g of ground asphalt powder (the asphalt powder is the undersize after passing through a 100-mesh sieve). Mix the mixture of copper acetate powder and asphalt powder evenly with a ball mill and place it in a beaker. Add 40 mL of deionized water to the beaker and stir until evenly mixed. Then place the beaker in an ultrasonic cleaner for 35 minutes at an ultrasonic power of 75 W. Then place the beaker in a constant temperature water bath at 75 °C and dry it for 5 hours. Then place the remaining sample in the beaker in a corundum ark and place the corundum ark in a nitrogen bath with a flow rate of 220 mL • min. -1 The crude carbon nanotubes were placed in a high-temperature tube furnace and heated to 1000°C at a heating rate of 5°C / min for 3 hours. The crude carbon nanotubes were obtained after cooling to room temperature. The crude carbon nanotubes were soaked in a 1 mol / L hydrochloric acid solution for 5 hours, washed to neutrality, and dried to obtain the final carbon nanotubes.

[0040] like Figure 4 As shown, the final product carbon nanotubes obtained in this comparative example can be seen that the obtained CNTs are shorter and irregular in shape, and the aspect ratio is relatively short. It can be seen that different solvent types have a great influence on the morphology of carbon nanotubes.

[0041] It can be seen from the results of the above comparative examples that suitable catalysts, solvents and ultrasonic power have a great influence on the morphology and conductivity of the prepared carbon nanotubes.

[0042] The preparation method of the present invention adopts the method of preparing carbon nanotubes by catalytic pyrolysis of asphalt, and copper acetate is used as the catalyst carrier. Carbon nanotubes (CNTs) are prepared by catalytic pyrolysis of asphalt. The effects of pyrolysis temperature and pyrolysis time on the growth of CNTs after pyrolysis of asphalt are studied. The advantages are: (1) adding a catalyst is conducive to promoting the formation of CNTs, wherein the optimal amount of copper acetate is 30wt.%; (2) temperature is the most important factor affecting the structure of carbon nanotubes, and the most suitable pyrolysis temperature is 1000℃; (3) high temperature pyrolysis time also seriously affects the yield and aspect ratio of CNTs. Experiments show that the optimal pyrolysis time should be 2.5h. Carbon nanotubes (CNTs) are prepared by catalytic pyrolysis of asphalt. This method is safe and environmentally friendly, requires low temperature, has no dangerous gas source, and has low cost. The carbon nanotubes prepared by the present invention have excellent specific surface area and electrical conductivity.

[0043] The specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing carbon nanotubes by catalytic pyrolysis of asphalt, characterized in that: The process includes the following: The asphalt powder and the catalyst powder are mixed to obtain a mixture A, wherein the mass ratio of the catalyst powder to the asphalt powder in the mixture A is (0.25-0.45):3; Dispersing the mixture A evenly in a volatile solvent to obtain a mixed solution A; volatilize the volatile solvent in the mixed solution A and dry it to obtain a mixture B; The mixture B is pyrolyzed under a protective atmosphere to obtain crude carbon nanotubes; The crude carbon nanotubes are reacted with an acid solution, and after the reaction is completed, they are washed and dried to obtain final carbon nanotubes.

2. The method for preparing carbon nanotubes by catalytic pyrolysis of asphalt according to claim 1, characterized in that: The catalyst powder is copper acetate powder.

3. The method for preparing carbon nanotubes by catalytic pyrolysis of asphalt according to claim 2, characterized in that: For every 3 g of asphalt powder, add 0.34-0.36 g of copper acetate powder.

4. A method for preparing carbon nanotubes by catalytic pyrolysis of asphalt according to any one of claims 1 to 3, characterized in that: The mesh size of the asphalt powder is above 100 meshes, and the mesh size of the catalyst powder is between 40 and 50 meshes.

5. The method for preparing carbon nanotubes by catalytic pyrolysis of asphalt according to claim 1, characterized in that: When the mixture B is pyrolyzed under a protective atmosphere, the pyrolysis temperature is 950-1050° C. and the pyrolysis time is 2-3 hours.

6. The method for preparing carbon nanotubes by catalytic pyrolysis of asphalt according to claim 1, characterized in that: When the crude carbon nanotubes react with the acid solution, the crude carbon nanotubes are immersed in a hydrochloric acid solution for the reaction.

7. The method for preparing carbon nanotubes by catalytic pyrolysis of asphalt according to claim 6, characterized in that: The concentration of the hydrochloric acid solution is 0.9-1.1 mol / L, and the soaking time is 4-6 hours.

8. The method for preparing carbon nanotubes by catalytic pyrolysis of asphalt according to claim 1, characterized in that: The volatile solvent is anhydrous ethanol. When the mixture A is evenly dispersed in the volatile solvent, every 3.75-3.45 g of the mixture A is mixed with 20-40 mL of anhydrous ethanol; Ultrasonic dispersion was used in the dispersion process, with an ultrasonic power of 60-80 W and an ultrasonic time of 10-30 min; When the mixture B is pyrolyzed under a protective atmosphere, the protective atmosphere is nitrogen, and the flow rate of the nitrogen is 200-230 mL·min -1 .

9. The method for preparing carbon nanotubes by catalytic pyrolysis of asphalt according to claim 1, characterized in that: When the volatile solvent in the mixed solution A is evaporated and dried, a constant temperature water bath is used for drying, the drying temperature is 74-76° C., and the drying time is 2-3 hours; The crude carbon nanotubes are reacted with an acid solution, and after the reaction is completed, they are washed and dried until neutral, and the drying temperature is 70-90° C. to remove moisture.

10. A carbon nanotube, characterized in that: The carbon nanotubes are prepared by the method for preparing carbon nanotubes by catalytic pyrolysis of asphalt as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing carbon nanotubes from coal tar pitch by in-situ pyrolysis method

    CN113772659A